Pengaruh Pembiayaan terhadap PDRB Sektor Perdagangan, Hotel, dan Restoran Ditinjau dari Pariwisata Syariah Provinsi Aceh - Vina Febyningtyas; Endang Hatma Juniwati; Setiawan Setiawan (Jurusan Akuntansi Politeknik Negeri Bandung, 2021)
Aceh Province is one of the provinces in Indonesia that implements and implements Islamic Law. Qanun is a statutory regulation applied in Aceh for the development of governance and community life in Aceh Province. This study aims to see whether there are a relationship and influence between BUS and UUS on the Gross Regional Domestic Product of the Trade, Hotel, and Restaurant sector. This study uses secondary data. The sample in this study was determined using probability sampling. This research method is an associative descriptive method with a quantitative approach. The analytical tool used in this study is a simple regression analysis with the help of applications. The results of the study are that there are a strong relationship and contribution as well as a positive influence between BUS and UUS Financing and the Gross Regional Domestic Product of Trade, Hotel, and Restaurant Sector of Aceh Province Period 2010-2018.